Safety and immunogenicity of inactivated COVID-19 vaccine CoronaVac and the RBD-dimer–based COVID-19 vaccine ZF2001 in chronic hepatitis B patients - Wu, Shiheng; Wang, Xiaolin; Feng, Mingyang; Liu, Xiaoman; Fan, Xinxing; Ran, Xiangui; Wang, Baogui; Wang, Hui (Frontiers in Medicine, 2023)
Background and Aims: Although COVID-19 vaccination is recommended for the patients with chronic liver disease, the clinical outcomes of COVID-19 vaccinated in patients with chronic hepatitis B (CHB) has not been well characterized. The study aimed to explore the safety and specific antibody responses following COVID-19 vaccination among CHB patients. Methods: Patients with CHB were included. All patients were vaccinated with 2 doses of inactivated vaccine (CoronaVac) or 3 doses of adjuvanted protein subunit vaccine (ZF2001). The adverse events were recorded and neutralizing antibody (NAb) were determined 14 days following the whole-course vaccination. Results: A total of 200 patients with CHB were included. Specific NAb against SARS-CoV-2 were positive in 170 (84.6%) patients. The median (IQR) concentrations of NAb were 16.32(8.44-34.10) AU/ml. Comparison of immune responses between CoronaVac and ZF2001 vaccines showed no significant differences in neither the concentrations of NAb nor the seropositive rates (84.4% vs 85.7%). Moreover, we observed lower immunogenicity in older patients and in patients with cirrhosis or underlying comorbidities. The incidences of adverse events were 37 (18.5%) with the most common adverse event as injection side pain (25 (12.5%)), followed by fatigue (15 (7.5%)). There were no differences in the frequencies of adverse between CoronaVac and ZF2001 (19.3% vs 17.6%). Almost all of the adverse reactions were mild and self-resolved within a few days after vaccination. Severe adverse events were not observed. Conclusions: COVID-19 vaccines, CoronaVac and ZF2001 had a favorable safety proﬁle and induced efﬁcient immune response in patients with CHB.